2018
DOI: 10.2337/dc18-1074
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Resting Metabolic Rate and Body Composition Measures Are Strongly Associated With Diabetic Retinopathy in Indonesian Adults With Type 2 Diabetes

Abstract: In this study, RMR and body composition measures were strongly associated with and contributed considerably to the presence and severity of DR. These findings, if confirmed, suggest that RMR and body composition may be strong markers that represent actual metabolic state in the pathophysiology of DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Although a high waist-to-hip ratio increased the risk of DR, a high BMI decreased the risk of DR in Asians with type 2 diabetes recruited from the Singapore National Eye Centre. 40 Sasongko et al 41 reported that high BMI was significantly associated with lower risk of DR in Indonesians with type 2 diabetes. Similarly, Chan et al 42 reported an inverse association between BMI and incidence of DR in separate prospective cohorts of Malays and Indians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a high waist-to-hip ratio increased the risk of DR, a high BMI decreased the risk of DR in Asians with type 2 diabetes recruited from the Singapore National Eye Centre. 40 Sasongko et al 41 reported that high BMI was significantly associated with lower risk of DR in Indonesians with type 2 diabetes. Similarly, Chan et al 42 reported an inverse association between BMI and incidence of DR in separate prospective cohorts of Malays and Indians.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 On the contrary, several studies have shown that obesity has the potential to diminish the severity of DR in Asians with type 2 diabetes. [40][41][42] Man et al 40 pointed out that generalized obesity and abdominal obesity may have different effects on DR. Although a high waist-to-hip ratio increased the risk of DR, a high BMI decreased the risk of DR in Asians with type 2 diabetes recruited from the Singapore National Eye Centre.…”
Section: Discussionmentioning
confidence: 99%
“…25 Following this line of thinking a recent work performed in a population of Indonesian patients with T2DM reported that body composition and overall estimated REE using BIA were strongly associated with and contributed considerably to the presence and severity of diabetic retinopathy independent of other systemic factors including diabetes duration, blood pressure, diabetes medication, and other diabetes complications. 26 Limitations of the present work are the crosssectional and retrospective nature of the analysis, the assessment of body composition using BIA methodology and the lack of knowledge for food preference. First, the retrospective analysis is the reason why the three groups of subjects resulted to be different in terms of some anthropometric parameters (sex, age and BMI; Table 1) with potential impact on energy metabolism; to minimize this potential bias we applied the appropriate adjustments for these differences in the multivariate analysis confirming the hypothesized association between REE and HOMA-IR (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…BMI is another index to assess the nutritional condition in routine clinical practice. Previous studies revealed that low BMI caused by uncontrolled glycaemia was correlated with an increased risk of DR. 32,33 Other studies discovered that high BMI or overnutrition, accompanied by hypertension and hyperlipidemia, brought about oxidative stress and inflammation, and then resulted in endothelial dysfunction, ultimately leading to the progression of DR. 34,35 Thus, the relationship between BMI and DR remains inconsistent. Abdominal obesity is considered as the risk for DR. 36 However, Muhammad et al discovered that WC was inversely associated with the severity of DR. 32 The current research suggested that there was no relationship between BMI and DR.…”
Section: Discussionmentioning
confidence: 99%